Immunomodulatory lysophosphatidylserines are regulated by ABHD16A and ABHD12 interplay - Kamat, Siddhesh S; Camara, Kaddy; Parsons, William H; Chen, Dong-Hui; Dix, Melissa M; Bird, Thomas D; Howell, Amy R; Cravatt, Benjamin F (Nature chemical biology, 2015)
ABHD16A is identified as a major enzyme catalyzing production of lyso-PS from phosphatidylserine (PS). A new ABHD16A inhibitor and knockout mice show a dynamic interplay occurring during inflammation between ABHD16A and disease-linked ABHD12, an enzyme that degrades lyso-PS. ABHD16A is identified as a major enzyme catalyzing production of lyso-PS from phosphatidylserine (PS). A new ABHD16A inhibitor and knockout mice show a dynamic interplay occurring during inflammation between ABHD16A and disease-linked ABHD12, an enzyme that degrades lyso-PS. Lysophosphatidylserines (lyso-PSs) are a class of signaling lipids that regulate immunological and neurological processes. The metabolism of lyso-PSs remains poorly understood in vivo . Recently, we determined that ABHD12 is a major brain lyso-PS lipase, implicating lyso-PSs in the neurological disease polyneuropathy, hearing loss, ataxia, retinitis pigmentosa and cataract (PHARC), which is caused by null mutations in the ABHD12 gene. Here, we couple activity-based profiling with pharmacological and genetic methods to annotate the poorly characterized enzyme ABHD16A as a phosphatidylserine (PS) lipase that generates lyso-PS in mammalian systems. We describe a small-molecule inhibitor of ABHD16A that depletes lyso-PSs from cells, including lymphoblasts derived from subjects with PHARC. In mouse macrophages, disruption of ABHD12 and ABHD16A respectively increases and decreases both lyso-PSs and lipopolysaccharide-induced cytokine production. Finally, Abhd16a −/− mice have decreased brain lyso-PSs, which runs counter to the elevation in lyso-PS in Abhd12 −/− mice. Our findings illuminate an ABHD16A-ABHD12 axis that dynamically regulates lyso-PS metabolism in vivo , designating these enzymes as potential targets for treating neuroimmunological disorders.